Fungicidal effect of chitosan via inducing membrane disturbance against Ceratocystis fimbriata. (15th July 2018) - Xing, Ke; Xing, Yun; Liu, Yuanfang; Zhang, Yu; Shen, Xiaoqiang; Li, Xiaoyan; Miao, Xiangmin; Feng, Zhaozhong; Peng, Xue; Qin, Sheng
Graphical abstract: Highlights: Chitosan induced leakage of intracellular components (e.g., K + ) of C. fimbriata . FDA-PI staining visualized decreased cell viability under the effect of chitosan. Massive DiBAC4 (3) accumulation indicated the dissipation of membrane potential. Chitosan decreased the activity of H + /K + ATPase. The fluorescence distribution and intensity of FITC was changed by chitosan. Abstract: In this study, the fungicidal effects and detailed action of chitosan against Ceratocystis fimbriata were evaluated. The results demonstrated that chitosan exhibited strong antifungal activity that restricted the mycelium extension and changed the hyphal morphology. Fluorescein diacetate (FDA) and propidium iodide (PI) double-staining directly visualized decreased cell viability in response to chitosan treatment. Investigation of the PI influx showed that chitosan induced irreversible cell membrane damage. The efflux of potassium ions from the cytosol into the extracellular matrix demonstrated that chitosan induced the leakage of intracellular components. Massive intracellular bis-(1, 3-dibutylbarbituric acid) trimethine oxonol [DiBAC4 (3)] accumulation indicated the dissipation of membrane potential. Furthermore, chitosan clearly decreased the activity of H + /K + ATPase. Fluorescence microscopy revealed that the fluorescence distribution and intensity of fluorescein isothiocyanate (FITC) changed as the incubation time increased. These results indicate that chitosan exerts a fungicidal effect via its ability to disturb fungal membranes.